Occurrence of Ectoparasites on Tilapia zillii (Red Belly Tilapia) Gervais 1848 in The Tono Reservoir, Navrongo, Ghana - Osei Ayeh, Samuel; Larbi Ayisi, Christian (Universitas Airlangga, 2024)
This study was carried out to assess the occurrence of endoparasites in (Tilapia zillii (Gervais, 1848)) from Tono reservoir, Navrongo Ghana. A total of 120 fish samples were collected from the upstream, midstream and downstream regions of the reservoir using cast nets. All the collected fish samples were transported to the research laboratory in the University for Development Studies and examined for ectoparasites during January 2022 to August 2022. Five ectoparasites namely Trichodina sp. of Protozoans ciliates, Dactyolgyrus sp. of Monogenean, Argulus sp. and Lernaea sp. of Crustaceans and the Diplostomum sp were identified. Overall prevalence of the fish parasites was 52.32 %. Intensity of the parasites observed ranged between 1.58% to 3.52%. Highest prevalence 70 % was reported in dry season while lowest (31.67%) was reported in the rainy season. Female fish samples had higher prevalence (64.47 %) than males (27.27 %). Fishes of downstream had highest prevalence (92.5 %) than upstream (17.5 %). Fish samples with maximum length and weight were highly (65.15 %) infected than small sized fish with low body length and weight (33.33 %). It is debatable if the degree of ectoparasite activity found in this study will constitute a serious danger to the local fish population. Yet, in order to stop disease outbreaks brought on by an increase in ectoparasites, the reservoir must be given significant attention by using optimum management strategies. This study shows that dry season affects the fish business and result in poor quality fish meat with risk of diseases infection.